Association between Insulin-Like Growth Factor-1 and Relative Skeletal Maturation: A Retrospective Cohort Study of Short Children and Adolescents. (14th August 2020) - Zhao, Qianqian; Zhang, Mei; Chu, Yuntian; Ji, Baolan; Pan, Hui; Sun, Hailing; Ban, Bo
Abstract : Objective . Delays in skeletal maturity are related to bone mass and fracture risk in children, but the factors that determine it are unknown. We aimed to identify the association between insulin-like growth factor-1 (IGF-1) and skeletal maturation before and after growth hormone (GH) treatment. Methods . In this retrospective cohort study, we observed 783 short children and adolescents, 229 of whom received GH therapy. Skeletal maturation was assessed based on the difference between bone age (BA) and chronological age (CA) (noted as BA-CA). Anthropometric data and laboratory values were measured, and BA was evaluated using the Greulich and Pyle method. Results . The delayed BA group was defined as BA ‐ CA < − 2 SD (n = 457 ), and the occurrence rate of BA delay was 58.37%. A nonlinear relationship was observed between the IGF-1 standard deviation score (IGF-1 SDS) and BA-CA before and after GH therapy. Before GH therapy, there was a significant positive association between the IGF-1 SDS and BA-CA when the IGF-1 level was greater than -2 SDS ( β 0.17, 95% CI 0.08, 027; P < 0.001 ). However, we did not observe a significant relationship between the IGF-1 SDS and BA-CA when the IGF-1 level was lower than -2 SDS ( β 0.07, 95% CI -0.12, 0.26; P = 0.454 ). After GH therapy, there was a significant positive association between the IGF-1 SDS and BA-CA when the IGF-1 level was lower than 2 SDS ( β 0.20, 95% CI 0.12, 028; P < 0.001 ). However, we did not observe a significant relationship between the IGF-1 SDS and BA-CA when the IGF-1 level was greater than 2 SDS ( β -0.03, 95% CI -0.33, 0.27; P = 0.866 ). Conclusion . BA is more delayed in short children and adolescents. There is a nonlinear relationship between IGF-1 and BA maturation in short children before and after GH treatment. These findings suggest that a low level of IGF-1 may contribute to BA delay in short children and adolescents.